Persistence of miconazole in vaginal secretions after single applications. Implications for the treatment of vaginal candidosis. Issue 6 (December 1981) - Odds, F C; MacDonald, F
Abstract : In vaginal secretions from 16 healthy women aged between 20 and 27 years miconazole persisted in biodetectable concentrations for at least 48 hours after insertion of a single miconazole vaginal pessary. This finding casts doubt on cure rates in vaginal candidosis determined soon after the end of treatment and suggests that current treatment courses with imidazole antifungal agents may be longer than their nominal three or five days.